PENGARUH PRODUCT PLACEMENT JENIUS PADA FILM "ALI & RATU-RATU QUEENS" TERHADAP BRAND ATTITUDE PENGIKUT INSTAGRAM @ALIDANRATUQUEENS - Rizka Noer Anisa (2022)
Based on data and research found showing that effectiveness and public attitudes towards TV advertising has decreased. Product placement promotion techniques are present as an alternative to overcome these problems. This study aims to determine how much influence the product placement of Jenius product in the film "Ali & Ratu-Ratu Queens" had towards the brand attitude of Instagram followers @alidanratuqueens. This research uses persuasive communication theory, Elaboration Likelihood Theory. This research method uses quantitative methods with the type of explanatory research. The sampling technique used is probability sampling with simple random sampling which produces 100 respondents to be studied by submitting 42 question items. The results obtained from this study are found a low level of correlation with the number 0.340 and the regression coefficient value of 0.147 which is in positive direction. Based on the results of the calculation of the coefficient of determination, the results of the influence of variable X and variable Y are 23.1%. The results of the t-test hypothesis test resulted in a comparison of 5.428 > 1.984 which stated that Ho was rejected and Ha was accepted.